Implementation and Strengthening of Multicultural Islamic Education in Public Schools - Mustahiqurrahman Mustahiqurrahman; Nurwahidah Nurwahidah; Rahmawati Rahmawati; Ratna Musyarrofatul Adnia (STKIP Taman Siswa Bima, 2023)
The rise of exclusive attitudes and the lack of understanding of differences, diversity, religious tolerance and moderation have led to the fading of multicultural values ​​in schools. In addition, the influence of the epidemic has at least damaged the character and character of students who tend to ignore the values ​​of (cultural) diversity and tolerance in the school environment. Multicultural Islamic education is taught in public schools with an emphasis on acknowledging and respecting the differences that are inevitable for people of any religion and improving from a strong emphasis on the cognitive domain to the affective and psychomotor domains as well as improving the quality of teachers both from the point of view of their understanding of their religion. themselves and other religions, so that they themselves have the right perspective of multiculturalism. Therefore. multicultural Islamic education is taught in public schools. This is important so that students have an understanding of differences, diversity, tolerance, mutual respect and mutual acceptance in every difference in life. The methodology used is observation, interviews and documentation and is supported by various relevant references so that it has scientific value in research. This paper attempts to provide an offer or solution on how Multicultural Islamic Education is taught in schools so as to form an inclusive (open) pattern of religious understanding and tolerance in students.